(untitled) (Research, Society and Development, 2022)
With increasing access to technology, healthcare applications have become quite popular, making life easier for healthcare professionals. In the field of nutrition, it is common to use software that helps in the area of ​​nutritional assessment. Thus, the objective of the study was to seek new technologies that can be applied to nutritional assessment. To this end, an integrative review was carried out using the System Search Flow (SSF) method, in which the terms “software” and “nutritional assessment” were searched in the MEDLINE, Scielo and Microsoft Academic databases. After the exclusion criteria and full reading of the text, it was seen that few articles deal with this topic, a total of 15 of the 304 articles analyzed. Of the articles found, most refer to new methods of estimating energy consumption, usually through images, with generally few articles discussing new technologies. It is important to consider that many of these new technologies in development and others that, although the emphasis is not on nutritional assessment, may be applicable in this area. Most nutrition software produced in Brazil is aimed at the general population and non-professional nutritionists, without a reliable database for what is offered. Finally, this study found several technologies that can be added to existing software, contributing to a continuous progress between information technology, nutrition and the improvement of the population’s health.